2021
DOI: 10.33225/pec/21.79.13
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Secondary Education on the Level of Financial Literacy: The Case of Slovakia

Abstract: Financial literacy, specifically its measurement and education in this field, is a very current topic. The main aim of this research was to find out whether secondary school education had a positive impact on the level of student’s financial literacy and to identify other important factors that affected its level. All 363 first-year bachelor's students of the Faculty of Operations and Economic of Transport and Communications (FPEDAS), University of Zilina, Slovakia, took part in the research. The research cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Rationale: Previous research shows that the overall level of education in Slovakia is higher in larger cities (Böhm et al 2021). Therefore, the same type of relation is expected in the case of financial literacy level.…”
Section: H Demographicfactorsmentioning
confidence: 92%
See 2 more Smart Citations
“…Rationale: Previous research shows that the overall level of education in Slovakia is higher in larger cities (Böhm et al 2021). Therefore, the same type of relation is expected in the case of financial literacy level.…”
Section: H Demographicfactorsmentioning
confidence: 92%
“…The secondary education factors have a statistically significant impact on financial literacy level. Rationale: Previous research indicated a relationship between education in secondary school and the level of financial literacy of first-year undergraduate students (Böhm et al 2021).…”
Section: H Secondaryeducationmentioning
confidence: 99%
See 1 more Smart Citation
“…Karakurum-Ozdemir et al (2019) found that individuals who cannot read or write in the official language of their country of residence have lower financial literacy scores. In addition to the number of lessons dedicated to mathematics and financial literacy, the overall academic performance of the student and the type of secondary school have a statistically significant impact on the level of student’s financial literacy (Böhm et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%